Pengaruh Konsentrasi Partai Politik di Daerah terhadap Pertumbuhan Ekonomi Daerah - Sugiyanto, Catur; Handoko, Budiono S.; Adinusa, Ilham (UI Scholars Hub, 2013)
In the Indonesia democracy, the multiparty system is used as one of the canal to aggregate the public aspirations. This mechanism is supported by Law No. 25/1999 about fiscal decentralization and a series of related regulations. It is also supported by direct election for regional head (Pilkada). As such, the winning political parties may influence the local government budget allocation which finally transform into the economic growth. This study estimates the influence of party politic concentration on the local economic growth. The data used is the local government election of 2004 and 2009 from 55 regions (cities). The concentration of political power in regional legislatives is measured by using Herfindahl Hirschman Index (HHI). The results of analysis confirm that the more concentrated political power in the regional legislative results lower economic growth.